Knowledgemon hunters: um jogo sério com geolocalização para apoiar a aprendizagem de crianças com autismo e dificuldades de aprendizado - Silva, Salatiel Dantas (Universidade Federal Rural do Semi-Árido, 2018)
Autism is a behavioral syndrome with different etiologies, deeply affecting the process of child development. Children with autism have some characteristics in common: the inability to relate to other people, leading them to isolation; communication disorders and obsessive concern for what is unchanging. In addition to the large number of cases of autistic children around the world, there is also the lack of preparation of some educational institutions to use resources that facilitate the learning process of these children. Therefore, this dissertation presents the project Knowledgemon-Hunters that has a Serious Game whose objective is to reduce social isolation and help in the learning of children with Autism Spectrum Disorder and with learning difficulties. The application developed presents digital monsters, which offer Learning Objects (LOs). These monsters can be geographically distributed in the real world. Each monster carries with it information defined by specialists responsible for children. With the use of a mobile computing device, children can hunt, capture monsters and view their contents. For validation, the K-Hunters game was applied with 10 professionals in autism who work in schools located in the city of Mossoró / RN. The information was obtained through questionnaires elaborated following the TAM methodology. The results demonstrate that professionals indicate that play has the potential to reduce social isolation and to aid in the learning of children with Autism Spectrum Disorder
Keywords: Realidade aumentada; Realidade virtual; Ontologias; Objetos de aprendizagem; Augmented reality; Virtual reality; Ontologies; Learning objects; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO